The effect of relevant corporate governance factors on the quality of financial reporting in family and non-family firms - Paiva, I.; Borralho, J; Gallardo-Vázquez, D.; Hernández-Linares, R. (the 42nd Annual Congress of the European Accounting Association, 2019)
The study analyses the quality of financial information in family firms versus non-family firms, relating good practices in corporate governance. We analysed 650 Spanish firms, listed and unlisted, in the period 2011-2016. The result shows a higher quality of financial information in family firms, a relationship which is reinforced by good governance factors, including the participation of women in management. The factors analysed are supported by agency and institutional theories. The study contributes to reducing the gap in the literature on the quality of financial information associated with family firms vs. non family firms.